Efek Ateroprotektif dan Vasoprotektif Katekin Teh Hijau terhadap Ekspresi eNOS pada Tikus Wistar Jantan dengan Diet Tinggi Lemak - Erna Susanti Retty Ratnawati (Universitas Muhammadiyah Malang, 2012)
Catechins , isolate from green tea GMB4 clones could be developed as a potential preventive agent for atherosclerosis. This activity is thought to be based on the structure epimerisation, hydroxy phenolic and galloil group of these isolates. The purpose of this study is to prove the influence catechins ,isolate from green tea, on the inhibition of the decrease eNOS expression in male wistar rats induced by high fat diet. The method used in this study consisted of ELISA for measurement of eNOS expression. The results showed that catechins inhibits the decreasing expression of eNOS at a dose of 6 mg / day and 24 mg / day was significantly but not dose 3mg / day. This suggests a dose 6mg / day and 24 mg / day is able to repair the damage signaling insulin on PI3K pathway caused by insulin resistance. These results are based on the ability of catechins as antioxidants. Catechins with hydroxy phenolic group is a potential electron donor to bind free radicals. Polyphenol catechins may also modulate signaling cellular processes such as NFkâ, activator protein 1 DNA binding, glutathione biosynthesis, PI3K / Akt, MAPK pathway and the Nrf2 transcription factor that regulates expression of several antioxidant genes. It can be concluded catechins inhibits decreasing expression of eNOS at a dose of 6 mg / day and 24 mg / day and can be developed as an agent and vasoprotective ateroprotective.